Education and Training Of Human Resources Technical Skills and The Preparation Of Standar Kompetensi Kerja Nasional Indonesia (Skkni) Of Production For Micro and Small Enterprises Processing Industry Sector In Sumedang In The Context Of Protecting Micro and Small Enterprises - Ariapramuda, Switcha Differentia; Mulyati, Etty; Suwandono, Agus (Enrichment: Journal of Multidisciplinary Research and Development, 2023)
Micro and Small Enterprises (MSEs) have their characteristics. One of the characteristics as well as the weakness of MSEs is the lack of ability and technical skills of human resources in product processing. Empowerment to improve technical skills is carried out in the form of education and skills training following the guidelines set out in laws and regulations. However, these guidelines have not met the growing competency needs of the business world. The research method used is a normative juridical approach with a statutory approach. The results of the research obtained include technical education and skills by the government that cannot be implemented properly due to the inaccuracy of the Sumedang Cooperative, Small, Medium Enterprises, Industry and Trade Office in implementing the provisions of the guidelines of the Minister of Cooperatives and Small and Medium Enterprises Regulation Number 18/PER/M/KUKM/IX/2015 accompanied by incomplete guidelines and incoherent explanations. The preparation of SKKNI production for micro and small enterprises in the processing industry sector as a form of legal protection needs to be done because there are still many MSEs in the processing industry sector that find it difficult to compete with large businesses in similar sectors due to the lack of ability and competence of MSEs in carrying out production because SKKNI has not been accommodated which is specialized and tailored for the interests of MSE production competence.